Evaluation of hemorrhoidal disease and lower extremity venous insufficiency in primary adult varicocele: A prospective controlled study. (October 2019) - Aslan, Rahmi; Erbin, Akif; Celik, Sebahattin; Ucpinar, Burak; Sahinalp, Sahin; Yıldızhan, Murat; Eryilmaz, Recep; Taken, Kerem
Background: The study investigated the association between varicocele, lower extremity venous insufficiency and hemorrhoidal disease. Methods: The study included 62 patients with varicocele and 60 voluntary subjects with no varicocele. Patients who were diagnosed as having varicocele on physical examination and Doppler ultrasonography were included in the study group. Examination of lower extremity venous insufficiency was performed by physical examination and Doppler ultrasonography. Examination of hemorrhoidal disease was performed by a general surgery specialist. Results: The patients with varicocele had a statistically significant ( p < 0.05) higher rates of venous insufficiency of the lower extremities and had a borderline significant difference of higher hemorrhoidal disease rates ( p = 0.05). Therewithal incidences of hemorrhoidal disease and lower extremity venous insufficiency were significantly higher in body mass index > 25 and age > 30 years of varicocele patients. Conclusion: There is a statistically significant relation between varicocele, lower extremity venous insufficiency, and hemorrhoidal disease. In particular, varicocele patients who are aged over 30 years and overweight are at higher risk.